Total NT-proBNP, a novel biomarker related to recurrent atrial fibrillation - Lidia Staszewsky (BMC, 2021)
Abstract Background Novel circulating biomarkers may help in understanding the underlying mechanisms of atrial fibrillation (AF), a challenge for AF management and prevention of cardiovascular (CV) events. Whether glycosylation affects the prognostic value of N-terminal pro-B type natriuretic peptide (NT-proBNP) in AF is still unknown. Objectives To test how deglycosylated total NT-proBNP, NT-proBNP and a panel of biomarkers are associated with: (1) recurrent AF, (2) first hospitalization for CV reasons. Methods A total of 382 patients of the GISSI-AF trial in sinus rhythm with a history of AF, echocardiographic variables, total NT-proBNP, NT-proBNP and nine additional biomarkers [Total N-terminal pro-B type natriuretic peptide (Total NT proBNP), N-terminal pro-B type natriuretic peptide (NTproBNP), Angiopoietin 2 (Ang2), Bone morphogenic protein-10 (BMP10), Dickkopf-related protein-3 (DKK3), Endothelial cell specific molecule-1 (ESM1), Fatty acid-binding protein 3 (FABP3), Fibroblast growth factor 23 (FGF23), Growth differentiation factor-15 (GDF15), Insulin-like growth factor-binding protein-7 (IGFBP7) and Myosin binding protein C3 (MYPBC3)]. were assayed at baseline, 6 and 12 months under blind conditions in a laboratory at Roche Diagnostics, Penzberg, Germany. The associations between circulating biomarkers and AF at the 6- and 12-month visits, and their predictive value, were assessed in multivariable models with logistic regression analysis and Cox proportional hazards regression analysis. Biomarkers associations were modelled for 1SD increase in their level. Results Over a median follow-up of 365 days, 203/382 patients (53.1%) had at least one recurrence of AF and 16.3% were hospitalized for CV reasons. Total NT-proBNP, NT-proBNP, Ang2 and BMP10 showed the strongest associations with ongoing AF. Natriuretic peptides also predicted recurrent AF (total NT-proBNP: HR:1.19[1.04–1.36], p = 0.026; NT-proBNP: HR:1.19[1.06–1.35], p = 0.016; Ang2: HR:1.07[0.95–1.20], p = 0.283; BMP10: HR:1.09[0.96–1.25], p = 0.249) and CV hospitalization (total NT-proBNP: HR:1.57[1.29–1.90], p < 0.001 1.63], p = 0.097). Conclusions The association of total NT-proBNP with the risk of AF first recurrence was similar to that of NT-proBNP, suggesting no influence of glycosylation. Analogous results were obtained for the risk of first hospitalization for CV reasons. Natriuretic peptides, Ang2 and BMP10 were associated with ongoing AF. Findings from the last two biomarkers point to a pathogenic role of cardiac extracellular matrix and cardiomyocyte growth in the myocardium of the right atrium and ventricle.